An Exploration Into Short-Interval Maintenance of Adult Hemispheric Cortical Thickness at an Individual Brain Level. (26th September 2017) - Wall, John; Xie, Hong; Wang, Xin
Adult cerebral cortical structure is thought to be statically maintained over short intervals. This view is based on group average findings but has never been studied at the individual level. This issue was examined with an unconventional longitudinal magnetic resonance imaging design which measured hemispheric mean cortical thickness of an adult man repeatedly at week intervals over 6 months. These measures were compared with measurement error estimates to test the current prediction that thickness measures would be statically maintained within measurement error variation. The results did not support this prediction. Thickness underwent incremental and decremental fluctuations which ranged up to 0.12 mm and 5.83% over week and multiweek intervals and which differed from measurement error variation. These exploratory analyses suggest a working hypothesis that short-interval cortical structural maintenance in an individual can involve fluctuations in thickness. If confirmed, this hypothesis has potential implications for cortical maintenance mechanisms and precision medicine approaches.